Abolish criminology - Saleh-Hanna, Viviane, 1976-; Williams, Jason M., 1986-; Coyle, Michael J. (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Abolish Criminology presents critical scholarship on Criminology and Criminal Justice ideologies and practices, alongside emerging freedom-driven discourses that encourage a vision and practice of new world formations. The book introduces readers to a detailed history and analysis of crime as a concept and its colonizing trajectories into existence and enforcement. These significant contexts buried within peculiar academic histories are often overlooked or unknown in academic and public discussions, and representations of crime and the criminal legal system. The book offers written, visual, and poetic teachings through which readers, students, and educators can engage with the often discussed but seldom understood concept of crime and its enforcement through the criminal legal system's research, theories, agencies and dominant cultures. Abolish Criminology serves the needs of undergraduate and graduate students and educators in the social sciences, arts, and humanities. It will also appeal to scholars, researchers, policy makers, activists, community organizers, social movement builders, and various reading groups comprised of the general public grappling with the increased critical public discourse on policing and criminal legal reform or abolition"--
Keywords: Critical criminology; Criminal justice, Administration of -- Moral and ethical aspects; SOCIAL SCIENCE / Criminology; SOCIAL SCIENCE / Penology